The need to integrate in primary healthcare: nurse identity constructions of pharmacists as entrepreneurs. Issue 8 (6th October 2020) - D'Souza, Natalia; Scahill, Shane
Abstract : Purpose: This study explores nurses' views as to whether they see community pharmacists as "entrepreneurial" and what this might mean for working together in primary care. Pharmacists are expected to fully integrate with their colleagues – particularly nurses – under the New Zealand health policy. Yet, there is scarce literature that examines multidisciplinary teamwork and integration through an entrepreneurial identity lens. This is particularly important since around the world, including New Zealand, community pharmacies are small businesses. Design/methodology/approach: This was an exploratory qualitative study. A total of 18 semi-structured interviews were conducted with nurses from primary care, nursing professional bodies and academics from nursing schools. Interviews were audio recorded and transcribed verbatim. Coding was undertaken through general inductive thematic analysis. Findings: In total three key themes emerged through analysis: the entrepreneurial profile of the community pharmacist, the lack of entrepreneurship across the profession, and the role identity and value that community pharmacists hold, as viewed by nurses. There appeared to be pockets of entrepreneurship in community pharmacy; nurses did not express a blanket label of entrepreneurship across the whole sector. Nurses also discussed several forms of entrepreneurship including commercial-oriented, clinical and social entrepreneurship. The social entrepreneurship identity of community pharmacists sat most comfortably with nurse participants. Overall, nurses appeared to value community pharmacists but felt that they did not fully understand the roles that this profession took on. Research limitations/implications: This paper contributes to the academic literature by identifying three domains of entrepreneurship relevant to community pharmacy as well as multi-level barriers that will need to be jointly tackled by professional bodies and policy-makers. Improving nurses' and other healthcare professionals' knowledge of community pharmacists' role and expertise is also likely to facilitate better inter-professional integration. Originality/value: There is scarce literature that attempts to understand how entrepreneurial identity plays out in health organisation and management. This study adds to the knowledge base of factors influencing integration in healthcare.